Doha declaration and agriculture in Developing countries - Chamarajakshi, R. (2002)
Developing countries had hoped that the Agreement on Agriculture negotiated as part of the Uruguay Round and signed at Marrakesh in 1994 by 120 countries would open up export markets for their products in the developed countries. In the past six years, however, these countries have found that several asymmetries and inequities in the agreement were not conducive to their interests. These concerns were voiced at several meetings and the WTO was urged time and again to first attend to these implementation issues before widening the scope of the WTO at the Fourth Ministerial Conference. This article discusses the progress reflected in this regard in the Doha declaration. - Reproduced.
Keywords: International trade